Gnostic Mysteries of Sex: Sophia the Wild One and Erotic Christianity - Churton, Tobias (Inner Traditions International, Limited, 2015)
There is a long tradition in Christianity of higher union with God through the sacrament of sex. For example, the Barbelo Gnostics practiced a spiritual sexuality known as "redemption by sin;" the mystery of Sophia can be seen in the philosophy of the Troubadours; and William Blake was influenced by a secret Renaissance sexual mysticism.